Pelestarian dan Integrasi Nilai-nilai Lokal dalam Tradisi Pendidikan Islam Aceh di Era Modernisasi: Dayah sebagai Warisan Budaya - Hayati, Salma; Lailatussaadah, Lailatussaadah; Hayati, Cut Intan; Arifin, Muhammad; Mutia, Sri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research examines the dynamics and preservation of Islamic educational traditions in the dayah of Aceh in the context of modernization that brings various challenges of social, technological, and formal education system changes. With a qualitative approach, this study examines the adaptation of dayah to maintain local values and intellectual traditions without eliminating the cultural roots and Islamic identity of the Acehnese people. Data were collected through participatory observation, in-depth interviews, and documentation in several integrated dayah in Aceh. The results of the study show that the modernization of dayah takes place in the aspects of institutions, curriculum, learning methods, and improving the competence of scholars and students, so that dayah continues to function as an educational center as well as a cultural and intellectual preservation. This research emphasizes the importance of integrating local values with modern innovations so that dayah education is relevant to the times and can maintain Aceh's cultural identity. These findings provide policy and practice recommendations education that is able to bridge tradition and modernization in Aceh.